A Corpus-Based Study of Public Attitudes towards Coronavirus Vaccines - Ganlin Xia; Yiting Chen; Lijing Lu (Complexity)
Since the beginning of 2020, COVID-19 has been sweeping the world on an unprecedented scale. As an important means of fighting the virus, vaccines have provoked heated discussions. Motivated by this practical concern, the present study aims at contributing to the understanding of public opinions about vaccines, which may provide implications for the government in their making and implementation of related policies. This research adopts a corpus-based approach in conjunction with a Critical Discourse Analysis (CDA). Data for this study drawn from the Coronavirus corpus show what people are actually saying in online newspapers and magazines in 20 different English-speaking countries. The collocation and frequency of the word “vaccine” are arranged in concordance contextually. Overall, this study reveals that the collocation of vaccine can be divided into several categories, and people’s major concerns about COVID-19 vaccination include global progress, equality, and the latest development.